12. Fauskevåg 1: Boplass fra mellommesolitikum - Kvalheim, Alice Sunde (Tromura, 2025)
Fauskevåg 1 is a Stone Age site located on a small, naturally defined surface, which was likely in the shoreline zone during its use. The site contains no structures other than a patch of red-burnt sand. There are at least two separate concentrations of artefacts on the surface, with datings to three or four different periods. The oldest dating, to approximately 8200 BC, is supported by the technological material. This material includes microliths and standardized blade production on conical or near-conical, thoroughly prepared cores with faceted platforms. Flake technologies in quartzite and quartz have also been identified, and these two are physically separated on the site surface. It is likely that the site was visited multiple times, as there are also datings to approximately 7600 BC, 5600 BC, and 5000 BC.